A tutorial on ‘capped utilisation’ as a metric and key performance target in NHS England’s Model Hospital operating theatres database: caution for international healthcare systems - Zhang, Chen; Dunstan, Claire; Pandit, Jaideep J. (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2024)
The National Health Service (NHS) in England has set hospitals a target of achieving > 85% in a metric called ‘capped theatre utilisation’ (CTU), as central to its post-pandemic surgical waiting list recovery planning. This could serve as a model internationally, as other countries seek to improve operating theatre efficiency. Our review presents an analysis of what CTU means in the context of other measures of theatre ‘utilisation’, serving as a tutorial for clinical leaders, managers and all staff involved in theatres better to understand the metrics sometimes being used to assess their performance. We present results of a theoretical sensitivity analysis to assess how CTU values vary for hypothetical operating lists of three different structures (number of cases, their duration, and intercase gap times), as the stated start and finish times are shifted backwards and forwards in time. We then present results of our interrogation of the NHS Model Health Operating Theatres database to assess hospitals' CTU performance over three years. We discovered that in theory, CTU was especially sensitive to both stated list start times and list structure. The relationship to start time was asymmetric: early starts in one list did not compensate for loss of CTU value with late start in another list, when values were averaged across lists. This sensitivity analysis also predicted wide weekly CTU fluctuations, with values < 85% more likely than > 85%, especially for tertiary referral centres predominantly undertaking long, complex procedures. Our interrogation of the database confirmed these predictions. Moreover, we discovered many instances of implausible CTU values and underlying patterns indicating fundamental flaws in the CTU algorithm, rather than data entry errors. We conclude that CTU, and the NHS target of 85%, is not a suitable metric for operating theatre performance. It has proved unachievable in any sustainable way, and its underlying algorithm produces aberrant values. We discuss the serious consequences of basing other national policies or funding models on a fundamentally flawed metric. These results have lessons for international healthcare systems.